Association of Age at Menarche with Anthropometric Measures in Punjabi Bania Girls - Pratibha Goyal; Zora Singh; Gurmeet Kaur Sethi (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Menarcheal age is the age at which menstruation begins. Menarcheal age is regarded as a sensitive indicator of physical, biological and psychological environment. Aim: 1) To determine the menarcheal age and to examine the relationship between current age at menarche with anthropometric measures in Punjabi bania girls. 2) To develop maturity standards for Bania girls. Materials and Methods: The present cross-sectional survey was carried out on 200 bania girls at the age of onset of menarche. Menarcheal data was obtained by status quo method by asking about whether menarche has been experienced or not. In the present survey adolescent girls were interviewed with the help of pre-designed questionnaire. Statistical analysis was carried out in SPSS software, version 16.0. The data were analysed using descriptive statistics and one-way ANOVA. Pearson’s correlation coefficient was used for correlation studies. Results: A total of 200 Punjabi bania girls were examined in the study. The median age of onset of menarche in these girls was 12.3 years. Menarcheal age was positively associated with biacromial width, bi-iliac width and arm span. Conclusion: The present research has revealed secular trend in the age of onset of menarche as indicated by median age of 12.3 years in Bania girls. The bi-acromial width, bi-iliac width and arm span were also correlated with the age of menarche.